ANALISA SOLUSI PENEKANAN TINGKAT NON PERFORMING FINANCING (NPF) PADA PEMBIAYAAN MURABAHAH (STUDI KASUS PADA BPRS RAHMANIA DANA SEJAHTERA BIREUEN) - Iskandar Iskandar; Rahmawati Rahmawati; Nurul Fahmi (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
Abstract The research objectives are: 1) To find out the factors that cause Non Performing Financing in murabaha financing at BPRS Rahmania Dana Sejahtera in Bireuen City. 2) To find out the Solution for Emphasis on Non-Performing Financing (NPF) Level on Murabaha Financing at BPRS Rahmania Dana Sejahtera in Bireuen City. The type of research the author uses here is a type of qualitative research with a descriptive approach, as well as data collection techniques using observation and interviews. Based on the results of the study, it can be concluded that: 1) Factors That Cause Non-Performing Financing are internal factors that arise from the bank with limited employee owned and new employees, while the internal factors of the customer, namely bankruptcy, incompetent in business, the filing of a business or collateral is not his, customers who use open funds in planning, as well as customers who are not responsible because of personal family factors. While external factors result from natural disasters, government regulations and conditions that are not in accordance with the plan. 2) Emphasis Solutions is carried out by applying a financing analysis consisting of a guarantee approach, character, repayment capability, feasibility study, and an approach to bank functions. Coupled with the application of the financing analysis principle of 5C (carater, capacity, capital, collateral, and condition of economy. Keywords: Non-Performing Financing, Murabahah Financing, Emphasis Solutions Abstrak Tujuan penelitian ini adalah: 1) Untuk mengetahui faktor-faktor penyebab Non Performing Financing pembiayaan murabahah pada BPRS Rahmania Dana Sejahtera Kota Bireuen. 2) Untuk mengetahui Solusi Tingkat Penekanan pada Non Performing Financing (NPF) pada Pembiayaan Murabahah pada BPRS Rahmania Dana Sejahtera Kota Bireuen. Jenis penelitian yang penulis gunakan disini adalah jenis penelitian kualitatif dengan pendekatan deskriptif, serta teknik pengumpulan datanya menggunakan observasi dan wawancara. Berdasarkan hasil penelitian dapat disimpulkan bahwa: 1) Faktor Penyebab Non Performing Financing adalah faktor internal yang muncul dari bank dengan terbatasnya pegawai yang dimiliki dan pegawai baru, sedangkan faktor internal nasabah yaitu kebangkrutan, tidak cakap dalam berbisnis, pengajuan usaha atau agunan bukan miliknya, nasabah yang menggunakan dana terbuka dalam perencanaan, maupun nasabah yang tidak bertanggung jawab karena faktor pribadi keluarga. Sedangkan faktor eksternal disebabkan oleh bencana alam, regulasi dan kondisi pemerintah yang tidak sesuai dengan rencana. 2) Solusi penekanan dilakukan dengan menerapkan analisis pembiayaan yang terdiri dari pendekatan penjaminan, karakter, kemampuan pembayaran kembali, studi kelayakan, dan pendekatan fungsi bank. Ditambah dengan penerapan prinsip analisa pembiayaan 5C (carater, capacity, capital, collateral, dan kondisi perekonomian. Kata kunci: Non Performing Financing, Pembiayaan Murabahah, Solusi Penekanan.